2006
DOI: 10.1103/physrevb.74.064501
|View full text |Cite
|
Sign up to set email alerts
|

Orbital magnetic dynamics in chiralp-wave superconductors

Abstract: We present a theory of orbital magnetic dynamics for a chiral p-wave superconductor with broken time-reversal symmetry. In contrast to the common Landau-Lifshitz theory for spin ferromagnets, the case of orbital magnetism cannot be described in terms of local magnetization density. Hence it is impossible to define unambiguously the spontaneous magnetic moment: the latter would depend on conditions of its experimental investigation. As an example of this we consider orbital magnetization waves and the domain st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…However, it appears that one should not take the notion of a magnetization due to p-wave pairing too literally. It was shown 28 that the chiral currents can in general not be written as the curl of a global magneti-zation, and that the effective value of M depends on the type of domain wall.…”
Section: Fig 2: (Color Online)mentioning
confidence: 99%
“…However, it appears that one should not take the notion of a magnetization due to p-wave pairing too literally. It was shown 28 that the chiral currents can in general not be written as the curl of a global magneti-zation, and that the effective value of M depends on the type of domain wall.…”
Section: Fig 2: (Color Online)mentioning
confidence: 99%
“…8 While the analysis was initially carried for the case of Landau-Lifshitz ͑LL͒ SCFM's with spin magnetism, the results have been generalized to the case of p-wave superconductors with orbital magnetism. 9 It was shown that these materials are in general described by more complicated magnetic dynamics than LL dynamics. However, two specific cases-namely, when the waves propagate either parallel or perpendicular to the spontaneous magnetization direction-can, in fact, be described by LL dynamics, though corresponding to different values of the magnetization, thus demonstrating the relevance of the analysis to unconventional superconductors with orbital magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in usual metals, dielectrics, or paramagnetics, this quantity cannot be trivially related to the bulk properties in SCFM's, but requires a separate study. Hence the next step was done by the present author and Sonin, [8][9][10] who have considered the electromagnetic response of a thick slab, concentrating on the Meissner regime, in which static magnetic fields are screened in the bulk. In this regime, static magnetic measurements are difficult, and hence microwave experiments may be of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…So "magnetization" M is determined by the DW structure and cannot be used for other phenomena connected with ferromagnetic ordering, e.g., analyzing the magnon spectrum. 20 Substituting Eq. ͑2͒ into Eq.…”
mentioning
confidence: 97%
“…As shown in Ref. 20, for orbital ferromagnetism the spontaneous magnetization cannot be defined unambiguously and the Landau-Lifshitz theory of ferromagnetism 18 based on this definition is not valid. Nevertheless, interaction of magnetization currents inside narrow DW with the magnetic field can be reduced to the expression looking like the standard Zeeman energy −h · M. However, here M is not a magnetic moment inside the domain but is defined so that 8M was the jump of the magnetic field on the DW ͓see Eq.…”
mentioning
confidence: 97%